PROTECTION OF THE RIGHT TO PRIVACY REGARDING THE AUTHORITY TO WIRETAP BY THE PROSECUTOR’S OFFICE BASED ON THE HUMAN RIGHTS-BASED APPROACH - Salsabila Anggraini Zakaria; Eko Mukminto Mukminto (Law Research Review Quarterly, 2026)
This article examines the legal basis of prosecutorial interception authority and its alignment with the protection of the right to privacy through a Human Rights-Based Approach (HRBA). Using a normative juridical method with statutory and conceptual approaches, the study evaluates the interception provisions in the Prosecutor’s Law and sectoral regulations. The findings indicate that prosecutorial interception remains declarative and lacks operational procedures that meet the HRBA principles of legality, necessity, proportionality, and accountability. This gap poses privacy risks and highlights the urgency of enacting a comprehensive Interception Act to ensure accountable and rights-compliant implementation.